In-Medium Strangeness Production and Hyperon-Potentials - Gaitanos, T.; Violaris, A.; Fabbietti, L.; Steffen, M.; Wirth, J. (HNPS Advances in Nuclear Physics, 2019)
A hot topic of current research concerns the Equation of State (EoS) of nucleons and, in particular, of hyperons in dense nucleonic media. The study of the EoS at nucleon densities far beyond saturation has been initiated several decades ago, however, the behavior of the EoS for strangeness particles is still an open issue. The strangeness part of the EoS is very important not only for the physics of exotic (hyper)nuclei, but also crucial for nuclear astrophysics, e.g., neutron star physics. Here we present our recent investigations related to the theoretical treatment of in-medium hyperon-interactions as well as first preliminary experimental results from pion-induced reactions. The theoretical study is based on the well-established Non-Linear Derivative (NLD) model, which is extended to the strangeness sector via SU(6) symmetry arguments. It turns out that the NLD-predictions are consistent with microscopic models based on the chiral-EFT theory. On the other hand, recent experimental HADES-data on hyperon and kaon production from pion-induced reactions indicate sensitivities on the underlying in-medium hyperon potentials. We thus conclude that, the recent experimental data from pion-induced reactions will definitely set stringent constraints on the still less understood hyperon-potentials in nucleonic matter.